Directional control for sailing trainer (electrical) - 380748 Eow, Yeong Taur (Skudai : Universiti Teknologi Malaysia, 2000)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2000